2008
DOI: 10.1002/smi.1217
|View full text |Cite
|
Sign up to set email alerts
|

A survey of nurses who experienced trauma in the workplace: influence of coping strategies on traumatic stress

Abstract: Decreasing traumatic stress is a key issue for nurses who experience trauma, but trauma of nurses in the workplace has only rarely been investigated in detail. This study was designed to characterize trauma of nurses in the workplace in detail, and to make comparison of coping strategies employed by nurses who recovered from traumatic stress and those of nurses with persistent traumatic stress. A study of trauma was conducted by asking 782 nurses to complete a questionnaire. Valid responses were provided from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 19 publications
2
14
0
Order By: Relevance
“…The meaning of resilience as perceived by first-line nurse managers included "positive thinking", "flexibility", "assuming responsibility", and "separating work and life. Such findings were consistent with study of Palestinians in the Gaza Strip which showed that Palestinians used religious factors in facing the stress and trauma, 98% said God help, 85.1% said they are proud of their achievements, and 71.55% said they had strong sense of purpose [37,38].…”
Section: Resiliencesupporting
confidence: 78%
See 1 more Smart Citation
“…The meaning of resilience as perceived by first-line nurse managers included "positive thinking", "flexibility", "assuming responsibility", and "separating work and life. Such findings were consistent with study of Palestinians in the Gaza Strip which showed that Palestinians used religious factors in facing the stress and trauma, 98% said God help, 85.1% said they are proud of their achievements, and 71.55% said they had strong sense of purpose [37,38].…”
Section: Resiliencesupporting
confidence: 78%
“…The results showed that trauma predominantly consisted of direct exposure to violent language or non-supportive behavior by physicians, followed by witnessing and learning of experiences. The results suggested that positive action, positive thinking', cognitive avoidance, uncontrolled thinking and talking' lead to persistence of traumatic stress [9]. Also, in another similar study the impact of occupational stress and coping strategies among emergency department (ED) nurses of China, demonstrated that 46.9% of ED nurses were in the high pressure level of occupational stresses.…”
Section: Coping Strategiesmentioning
confidence: 87%
“…Similarly, Weinberg and Creed (2000) added that health workers with post traumatic distress are more vulnerable to psychiatric disorders and ongoing social stress outside of work. Furthermore, the analysis of a study conducted by Niiyama et al (2009) revealed that only 17% of nurses recovered from traumatic stress while the other 83% had persistent traumatic stress. Moreover; studies showed that prevalence of PTSD is associated with burn out syndrome, which together has a great impact on work and non-work related activities and perceptions (Mealer et al, 2009).…”
Section: Conclusion and Implications For Interventionmentioning
confidence: 99%
“…Regardless that other several studies explored the prevalence of PTSD among nurses and other health workers after exposure to different types of traumas, the prevalence of PTSD among participants of this study still much higher than those reported by all of these studies. For example, prevalence of PTSD was 13.7% among nurses who had encountered patient suicide (Takahashi et al, 2011), 21% among nurses who had been exposed to verbal abuse or violence (Inoue, Tsukano, Muraoka, Kaneko, & Okamura, 2006), 64.5% among health care workers working in a high-risk units during the severe acute respiratory syndrome (SARS) outbreak (Styra et al, 2008), 29-35% among health care providers during severe SARS (Maunder, 2004), 24-29% among ICU nurses (Mealer, Shelton, Berg, Rothbaum, & Moss, 2007), 22% among nurses (Mealer, Burnham, Goode, Rothbaum, & Moss, 2009), 20% among nurses (Battles, 2007), 51% of nurses exposed to trauma (Niiyama et al, 2009), 26.3% of deployed military healthcare officers (Hickling, Gibbons, Barnett, & Watts, 2011), 26.7% of healthcare workers (Weinberg & Creed, 2000), and 9% among health care workers deployed to combat setting (Kolkow, Spira, Morse, & Grieger, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Weinberg and Creed (2000) added that health workers with post traumatic distress are more vulnerable to psychiatric disorders and ongoing social stress outside of work. Furthermore, the analysis of a study conducted by Niiyama et al (2009) revealed that only 17% of nurse recovered from traumatic stress while the other 83% had persistent traumatic stress. Moreover; studies showed that prevalence of PTSD is associated with burn out syndrome, which together has a great impact on work and non-work related activities and perceptions (Mealer et al, 2009).…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%